Polypharmacy and patterns of prescription medication use among cancer survivors. Issue 13 (12th April 2018) - Murphy, Caitlin C.; Fullington, Hannah M.; Alvarez, Carlos A.; Betts, Andrea C.; Lee, Simon J. Craddock; Haggstrom, David A.; Halm, Ethan A.
Abstract : BACKGROUND: The population of cancer survivors is rapidly growing in the United States. Long‐term and late effects of cancer, combined with the ongoing management of other chronic conditions, make survivors particularly vulnerable to polypharmacy and its adverse effects. In the current study, the authors examined patterns of prescription medication use and polypharmacy in a population‐based sample of cancer survivors. METHODS: Using data from the Medical Expenditure Panel Survey (MEPS), the authors matched cancer survivors (5216 survivors) with noncancer controls (19, 588 controls) by age, sex, and survey year. Polypharmacy was defined as ≥5 unique medications. The authors estimated the percentage of respondents prescribed medications within therapeutic classes and total prescription expenditures. RESULTS: A higher percentage of cancer survivors were prescribed ≥5 unique medications (64.0%; 95% confidence interval [95% CI], 62.3%‐65.8%) compared with noncancer controls (51.5%; 95% CI, 50.4%‐52.6%), including drugs with abuse potential. Across all therapeutic classes, a higher percentage of newly (≤1 year since diagnosis) and previously (>1 years since diagnosis) diagnosed survivors were prescribed medications compared with controls, with large differences observed with regard to central nervous system agents (65.8% [95% CI, 62.3%‐69.3%] vs 57.4% [95% CI, 55.3%‐59.5%] vs 46.0% [95% CI, 45.0%‐46.9%]). Specifically, nearly 10% of survivors were prescribed benzodiazepines and/or opioids compared with approximately 5% of controls. Survivors had more than double the prescription expenditures (median of $1633 vs $784 among controls). Findings persisted across age and comorbidity categories. CONCLUSIONS: Cancer survivors were prescribed a higher number of unique medications, including drugs with abuse potential, thereby increasing their risk of adverse drug events, financial toxicity, poor adherence, and drug‐drug interactions. Cancer 2018;124:2850‐2857 . © 2018 American Cancer Society Abstract : In a nationally representative sample, cancer survivors are found to be prescribed more unique medications, ≥5 concurrent medications, and more medications with abuse potential compared with adults without cancer. Survivors may be at an increased risk of the consequences of polypharmacy, including adverse drug events, financial toxicity, poor adherence, and drug‐drug interactions.